PERANCANGAN APLIKASI MANAJEMEN KEUANGAN BERBASIS WEB PADA GKRI EFESUS - Dennis Kurniawan Adhi; Tony (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
GKRI Efesus is a church that has worship services such as general worship, youth, communion, and sunday school. There is member and financial data to fulfill the needs of the congregation and the church. Data that must be stored such as member identities, marriage data, baptism data, and church commissions. The caretaker stores the data manually through a book, making it prone to data loss and difficult to read the data. There are two administrators to record the data, namely the membership admin, and the super admin. The web-based data management application will use the PHP programming language and the Laravel framework and using the MySQL database will help process the data. The design method in this application uses the SCRUM method. This application can manage data for church needs such as member data by membership administrators, money data by finance with.